DEVELOPING STUDENTS’ CRITICAL THINKING WITH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING ACTIVITIES - Aliya Mukhlisotul Latifah Putri Dhani; Nuraeni Nuraeni; Eska Perdana Prasetya (English Didactic, 2021)
Activities in the implementation of the problem-based learning model train students in finding information independently related to the problems obtained and train students to be able to solve the problems they face in order to develop students' thinking skills. The purpose of this study is to describe what activities can develop students' critical thinking skills in implementing the PBL model. The method used in this research is a case study in qualitative research by collecting data using self-observation (video recorder). The data collection technique used to obtain the data on the implementation of problem-based learning model in developing students’ critical thinking by doing the activities in learning. The result showed that the activities in problem-based learning model can be implemented in developing students’ critical thinking. This is supported by observational data from self-observation on students’ activities and responses to the implementation of problem-based learning model.